(untitled) (Tạp chí Y học Cộng đồng, 2026)
Objective: To evaluate the prophylactic efficacy of Granisetron compared with Ondansetron in preventing postoperative nausea and vomiting during the first 24 hours after gastrointestinal surgery in pediatric patients. Methods: A randomized controlled clinical trial was conducted on 100 pediatric patients aged ≥ 2 years, classified as ASA I-II, undergoing gastrointestinal surgery at the Vietnam National Children’s Hospital. Patients were randomly allocated into 2 groups: Ondansetron group (n = 50) received intravenous Ondansetron 0.15 mg/kg, and Granisetron group (n = 50) received intravenous Granisetron 0.01 mg/kg at the end of surgery. Results: The mean time to the first episode of postoperative nausea and vomiting was over 6 hours in both groups, with no statistically significant difference. However, in the late postoperative period (12-24 hours), Granisetron demonstrated superior efficacy: only 4/50 patients experienced nausea and vomiting compared with 16/50 patients in Ondansetron group. Resting pain scores (VAS) at 8 and 24 hours postoperatively were also significantly lower in the Granisetron group. Hemodynamic (heart rate, blood pressure) and respiratory (respiratory rate) parameters remained stable in both groups, and no prolonged sedative adverse effects were observed. Conclusion: Granisetron is more effective than Ondansetron in maintaining prophylaxis against postoperative nausea and vomiting in pediatric gastrointestinal surgery, particularly during the late postoperative period (12-24 hours).